2013
DOI: 10.1371/journal.pone.0079877
|View full text |Cite
|
Sign up to set email alerts
|

A RhoC Biosensor Reveals Differences in the Activation Kinetics of RhoA and RhoC in Migrating Cells

Abstract: RhoA and RhoC GTPases share 92% amino acid sequence identity, yet play different roles in regulating cell motility and morphology. To understand these differences, we developed and validated a biosensor of RhoC activation (RhoC FLARE). This was used together with a RhoA biosensor to compare the spatio-temporal dynamics of RhoA and RhoC activity during cell protrusion/retraction and macropinocytosis. Both GTPases were activated similarly at the cell edge, but in regions more distal from the edge RhoC showed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 40 publications
1
55
1
Order By: Relevance
“…53 This analysis showed that areas of RhoC activation appeared to be more diffuse and evenly distributed at the edge of the cell. 53 Furthermore, the authors showed that RhoA and RhoC activities have different kinetics during lamellipodial protrusions. These different activation dynamics suggest that the key determining factors that control subcellular GTPase activation dynamics is likely the spatial distribution of their upstream regulators.…”
Section: The Abcs Of Rho Gtpasesmentioning
confidence: 90%
See 2 more Smart Citations
“…53 This analysis showed that areas of RhoC activation appeared to be more diffuse and evenly distributed at the edge of the cell. 53 Furthermore, the authors showed that RhoA and RhoC activities have different kinetics during lamellipodial protrusions. These different activation dynamics suggest that the key determining factors that control subcellular GTPase activation dynamics is likely the spatial distribution of their upstream regulators.…”
Section: The Abcs Of Rho Gtpasesmentioning
confidence: 90%
“…49,53,56 At invadopodia, RhoC has a geometrically confined activation pattern, while RhoA displays a more random activation pattern. 56 At leading edge protrusions, RhoC activation is confined spatially behind RhoA activation.…”
Section: The Abcs Of Rho Gtpasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2D migration, RhoA localizes to the rear of the cell where it is thought to promote rear retraction. At the front of the cell, Rho A is found at the border of the lamellipod and lamella, while RhoC is found at the leading edge (Zawistowski et al, 2013)(Bravo-Cordero et. al., 2014).…”
Section: Functionsmentioning
confidence: 99%
“…Both RhoA and RhoC play roles in the extension of membrane protrusions during migration on a 2D surface, with RhoC preceding protrusion formation (Pertz et al, 2006, Zawistowski, Sabouri-Ghomi, 2013). Rho A also regulates the contraction at the lateral and rear of the cell, further supporting forward migration.…”
Section: Functionsmentioning
confidence: 99%